2021
DOI: 10.1139/cjpp-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil prevents the nephrotoxic effect of cyclosporine-A in albino rats through modulation of HIF-1α/VEGF/eNOS signaling

Abstract: Despite cyclosporine-A (CsA) is a widely used immunosuppressive drug; its nephrotoxic effect puts a limitation for chronic administration. Herein we tried to investigate its renal effect on endothelial dysfunction targeting the hypoxia-inducible factor (HIF-1α)/vascular endothelial growth factor (VEGF)/endothelial nitric oxide synthase (eNOS) pathway and the possible modulation by nicorandil. Eight groups of adult male Wistar rats were included; 1: control, 2: vehicle group (received oil), 3: glibebclamide 5mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…In this case, LPS did not affect eNOS activation, however, treatment with 0.2 μM CsA alone decreased the enzyme activation (Figures 4A,B). This effect of CsA on eNOS activity has been previously reported and is related to the effects of the drug on intracellular pathways (Arab et al, 2021;Harb et al, 2021). eCypA also reduced eNOS phosphorylation, showing levels of 33.0 ± 10.4% (p < 0.01).…”
Section: Ecyps a B And C Affect Enos And Nfkb Activation In Pancreati...supporting
confidence: 82%
“…In this case, LPS did not affect eNOS activation, however, treatment with 0.2 μM CsA alone decreased the enzyme activation (Figures 4A,B). This effect of CsA on eNOS activity has been previously reported and is related to the effects of the drug on intracellular pathways (Arab et al, 2021;Harb et al, 2021). eCypA also reduced eNOS phosphorylation, showing levels of 33.0 ± 10.4% (p < 0.01).…”
Section: Ecyps a B And C Affect Enos And Nfkb Activation In Pancreati...supporting
confidence: 82%
“…In contrast, NR treatment reversed the impact of GM on NO production as well as eNOS expression 51 . Recently, NR has been reported to increase eNOS protein expression in bleomycininduced pulmonary fibrosis 52 , as well as nephrotoxic model of cyclosporine-A in rats 23 . Interestingly, it has been demonstrated that NR has the ability to enhance the expression eNOS in cardiac tissue via activation of an ATP-dependent K channel 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the renal effect of NR, it was reported to protect podocytes from hyperglycemia-induced oxidative stress 13 and ameliorated renal injury induced by unilateral ureteral obstruction in rats 22 . Recently, NR was shown to prevent the deleterious effects of cyclosporine-A in the kidney via modulation of HIF-1α/VEGF/eNOS signaling 23 . However, the nephroprotective effect of NR against GM-induced renal toxicity has not been yet clarified.…”
Section: Introductionmentioning
confidence: 99%
“…C Cr was calculated using the previously documented formula 36 normalC Cr ml / min / kg = Urinary Creatinine mg / dl × Urine volume ml × 1000 normalg Serum creatinine mg / dl × Body weight normalg × 1440 min …”
Section: Methodsmentioning
confidence: 99%